Mahmoud Darwish. Unfortunately, it was Paradise. Trans. By Munir Akash and Carolyn Forche, with Sinan Antoon and Amira El-Zein. Los Angeles and Berkeley: University of California Press, 2003 - López Habib, José Luis (Estudios de Asia y África, 2003)
-